Outcomes of infants with birthweights less than 501 g compared to infants weighing 501–750 g at a center utilizing first intention high frequency jet ventilation - Elgin, Timothy G.; Berger, Jennifer N.; Kaluarachchi, Dinushan C.; Dagle, John M.; Thomas, Brady; Colaizy, Tarah T.; Klein, Jonathan M. (Frontiers in Pediatrics, 2024)
Background. Data on clinical outcomes of infants with birthweights less than 501 grams (ELBW <501 ) are limited.Objective. To evaluate management strategies and clinical outcomes of ELBW <501 infants compared to infants weighing 501-750 grams (ELBW 501-750 ).Methods. A retrospective study of all ELBW <501 and ELBW 501-750 infants born between 2012-2022 at a center utilizing first intention high frequency jet ventilation was performed. Patient characteristics, clinical and outcome data were compared between the two groups.Results. A total of 358 infants (92 ELBW <501 infants and 266 ELBW 501-750 ) were included. The survival rate for the ELBW <501 group was 60.9% compared to 86.5% for ELBW 501-750 . ELBW <501 infants required more frequent use of 2.0mm endotracheal tubes, required higher FiO2 and longer duration of mechanical ventilation. Compared to ELBW 501-750 group, the ELBW <501 group were more likely to be SGA (68.2% vs 16.5%) and more premature (23.2 vs 24.3 weeks) with lower survival, longer length of stay, higher incidence of ROP and lower weight at discharge but comparable rates of IVH, grade 3 BPD, discharged on supplemental oxygen, and tracheostomy.ELBW <501 infants are at risk for significant morbidity and mortality. However, with specialized obstetric and neonatal care, survival rates of 60% are possible with respiratory outcomes comparable to ELBW 501-750 infants. However, the increased risk of severe ROP for ELBW <501 requiring either surgical or medical intervention is concerning and warrants optimal surveillance.